Effects of storage temperature on the quality and quantity of DNA extracted from maize leaves - Kostadinović Marija S.; Ristić Danijela S.; Lučev Milica J.; Ignjatović-Micić Dragana D.; Vančetović Jelena P. (Journal of Agricultural Sciences (Belgrade))
This study was carried out to evaluate the effect of temperature during storage of maize leaves and extracted DNA on its quality and quantity in order to be efficiently amplified using PCR. Leaves were collected from the fourweek-old plants and divided into three groups of 20 samples. The first group of leaves was processed immediately, while the other two were stored at -20°C or - 80°C for 30 days. The DNA extracted from the fresh leaves was divided into three portions with the first being amplified immediately and the other two were stored at -20°C or -80°C for 30 days. The DNA quality and quantity were examined using a biospectrometer, after which the samples were diluted for the PCR assay. The quality of all DNA samples was at an acceptable level with their average OD260/280 ratio in the range from 1.85 to 1.87. The concentration of the DNA extracted immediately from fresh leaf tissue was not statistically different from the stored samples. Both the quality and quantity of DNA in all samples were sufficient for successful PCR amplification with two opaque2-specific molecular markers. Phi057 amplified a ~170bp fragment in QPM and ~160bp in non-QPM, while umc1066 amplified a ~150bp fragment in QPM and ~160-170bp in non-QPM. Our results suggest that appropriate storage conditions do not affect the DNA quality and quantity. This could be useful in marker-assisted selection of target genes, when a large number of samples must be processed prior to pollination, allowing breeders to discard plants lacking the desired alleles and reduce the size of the breeding population.